Increasing Parents Knowledge Through Education of Simple Steps Demonstration Methods in Wound Care in Children with Special Needs Community Sidorejo, Kediri District - Erva Elli Kristanti; Dyah Ayu Kartika W.S; Putu Indraswari (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
In general, an injury is considered minor if it does not cause disease or interfere with daily activities. Minor wounds can also be small and fairly clean. Wounds that are not treated properly can cause slow wound healing and even infection. The purpose of this study was to identify the effect of health education on wound care with changes in parental knowledge in the children with special needs community, Sidorejo, Kediri District. The research method used was a quasy experimental one group pre test post test. Data collection was carried out using a questionnaire given twice to obtain knowledge data before and after education The research method used was a quasy experimental one group pre test post test. Data collection was carried out using a questionnaire given twice to obtain knowledge data before and after education. Based on the results of the study, it was found that the majority of parents in the children with special needs community had sufficient knowledge of 21 respondents (84%) Both 2 respondents (8%) and 2 respondents lacking (8%). While the results of the analysis of the results of the study obtained ρ 0.000 so that it was concluded that there was an effect of knowledge before and after education on simple wound care in the children with special needs community community in Sidorejo, Kediri